Стихотворения и поэмы 1912 - 1931 - Пастернак Борис Леонидович (1989)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 27928 / Цена: 5.00 / Сис.шифр: Р2 / Авт.знак: П 19 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6